AN EXPERIMENTAL STUDY TO EVALUATE THE IMPACT OF HEALTH EDUCATION ON DENGUE FEVER AWARENESS AND MANAGEMENT AMONG CAREGIVERS OF PATIENTS ADMITTED TO COMMUNITY HEALTH CENTRE (CHC) IN GANDHINAGAR, BHOPAL, MADHYA PRADESH (Cuestiones de Fisioterapia, 2025)
Dengue fever (DF) has emerged as a significant public health concern, with a notable increase in cases in recent years. Globally, it is estimated that there are 400 million infections and 100 million symptomatic cases annually. In India, an average of 100,690 cases was reported annually between 2013 and 2017. In 2018, India reported 110,473 cases of Dengue fever.